Numerical study on the perforation of steel plates by multiple projectiles. Issue 7 (25th October 2018) - Xiao, Yihua; Dong, Huanghuang; Zhan, Haifei; Zhu, Aihua
Abstract : Purpose: Metal plates are usually used as protective shields of engineering structures, which probably undergo multiple projectile impacts resulting from gunshot and blast. Though a large number of studies have been conducted on the performance of metal plates under a single projectile impact, few studies have explored their performance under multiple projectile impacts. This paper aims to explore the performance of Weldox 460 E steel plates against multiple projectile impacts through numerical simulation. Design/methodology/approach: A three-dimensional coupled finite element (FE) and smoothed particle hydrodynamics (SPH) model was developed to simulate the perforation of a 12-mm-thick Weldox 460 E steel plate by an ogival projectile. The model was verified by existing experimental data. Then, it was extended to investigate the same target plate subjected to impacts with multiple projectiles. Simultaneous impacts with different number of projectiles, as well as sequential impacts with two projectiles, were considered. Findings: Effects of spacing between projectiles on residual velocity of projectile, ballistic limit and failure mode of target were revealed for simultaneous impacts. Effects of spacing and axial distance between projectiles on residual velocity of projectile were explored for sequential impacts. Originality/value: This work developed an advanced FE–SPH model to simulate perforation of steel plates by multiple projectiles, and revealed the effects of multiple impacts on ballistic performance of steel plates. It provides guidance for the design of protective structures/shields in various engineering applications.